A pH‐Neutral, Metal‐Free Aqueous Organic Redox Flow Battery Employing an Ammonium Anthraquinone Anolyte. (12th September 2019) - Hu, Bo; Luo, Jian; Hu, Maowei; Yuan, Bing; Liu, T. Leo
Abstract: Redox‐active anthraquinone molecules represent promising anolyte materials in aqueous organic redox flow batteries (AORFBs). However, the chemical stability issue and corrosion nature of anthraquinone‐based anolytes in reported acidic and alkaline AORFBs constitute a roadblock for their practical applications in energy storage. A feasible strategy to overcome these issues is migrating to pH‐neutral conditions and employing soluble AQDS salts. Herein, we report the 9, 10‐anthraquinone‐2, 7‐disulfonic diammonium salt AQDS(NH4 )2, as an anolyte material for pH‐neutral AORFBs with solubility of 1.9 m in water, which is more than 3 times that of the corresponding sodium salt. Paired with an NH4 I catholyte, the resulting pH‐neutral AORFB with an energy density of 12.5 Wh L −1 displayed outstanding cycling stability over 300 cycles. Even at the pH‐neutral condition, the AQDS(NH4 )2  /NH4 I AORFB delivered an impressive energy efficiency of 70.6 % at 60 mA cm −2 and a high power density of 91.5 mW cm −2 at 100 % SOC. The present AQDS(NH4 )2 flow battery chemistry opens a new avenue to apply anthraquinone molecules in developing low‐cost and benign pH‐neutral flow batteries for scalable energy storage. Abstract : Ein Anthrachinonsalz, AQDS(NH4 )2, wurde als neues Anolytmaterial für pH‐neutrale wässrige organische Redox‐Flow‐Batterien (AORFBs) mit einer Löslichkeit von 1.9 m in Wasser konzipiert. Eine mit AQDS(NH4 )2 gefertigte AORFB zeigte eine hervorragende Akkuleistung, einschließlich 100 % Zyklenfestigkeit über 300 Zyklen, eine Energieeffizienz von 70.6 % bei 60 mA cm 2 und eine Leistungsdichte von 91.5 mW cm −2 bei 100 % Ladezustand.